2010
DOI: 10.1007/s12613-010-0350-4
|View full text |Cite
|
Sign up to set email alerts
|

Particle simulation of the failure process of brittle rock under triaxial compression

Abstract: In order to investigate the failure process of brittle rock under triaxial compression through both experimental and numerical approaches, the particle simulation method was used in numerical simulations and the simulated results were compared with those of the experiment. The numerical simulation results, such as fracture propagation, microcrack distribution, stress-strain response, and damage patterns, were discussed in detail. The simulated results under various confining pressures (0-60 MPa) are in good ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Many conventional triaxial tests have shown that rock specimens fracture with a highly uneven plane even though the confining pressure is greater than 20 MPa. However, specimens compressed by Mogi‐type TTAs always manifest a fracture pattern of shearing on a planar fault that is parallel to σ 2 .…”
Section: Discussionmentioning
confidence: 74%
“…Many conventional triaxial tests have shown that rock specimens fracture with a highly uneven plane even though the confining pressure is greater than 20 MPa. However, specimens compressed by Mogi‐type TTAs always manifest a fracture pattern of shearing on a planar fault that is parallel to σ 2 .…”
Section: Discussionmentioning
confidence: 74%
“…Thus, the numerical method is an alternative to feasibly solve this problem. In previous studies, the bonded particle model (BPM) based on the discrete element method (DEM) was widely used to reproduce the progressive failure behavior of the intact rock [ 29 , 30 , 31 , 32 , 33 , 34 ] and the rock containing flaws under quasi-static loads [ 35 , 36 , 37 ]. These numerical results were in line with experimental results, which indicated that the BPM was able to simulate the progressive failure of the brittle rock.…”
Section: Introductionmentioning
confidence: 99%
“…Taking experimental study on mechanical properties of rock as an example, Chen et al ( 2016a , b ) conducted a series of conventional triaxial compression tests on granite to investigate the pre-failure damage and found that the damage increases slowly before the reversal of volumetric strain and accelerates quickly afterwards. Xia and Zhou ( 2010 ) studied the failure process of brittle rock under uniaxial and triaxial compression. The results revealed that rock failure is caused by axial splitting under uniaxial compression; as the confining pressure increases, rock failure occurs in a few localized shear planes and the rock mechanical behavior is changed from brittle to ductile.…”
Section: Introductionmentioning
confidence: 99%